(untitled) (Perspectivas em Ciência da Informação, 2023)
The essay was built from the analysis of the relevant literature and also from the author’s experience in scientific policy evaluation processes, evaluation of strict sense graduate programs and in editorial activity in scientific journals published in the country and abroad. The evaluation of scientific production through scientific articles has two main aspects: the evaluation of the articles themselves and the evaluation of the journals in which they are published. In the evaluation of the articles themselves, three different and complementary strategies can be fundamentally used: classification according to the formal characteristics of the article, counting of citations received, and qualitative evaluation based on post-publication peer review procedures. In evaluating journals as indirect indicators of production quality, different bibliometric indicators are used, either as a weighting factor for articles numbers, or as criteria for building classifications such as Qualis journals from CAPES. As in any complex issue, there cannot be a single way of carrying out the evaluation, and the use of different strategies can counterbalance existing limitations in each of them, giving a more comprehensive and multifaceted perspective for the evaluators.